2018
DOI: 10.1515/bams-2018-0034
|View full text |Cite
|
Sign up to set email alerts
|

The similarity of selected statins – a comparative analysis

Abstract: The paper presents the physicochemical and structural characteristics as well as the comparison of selected statins. Statins are relatively popular compounds used in modern medicine. They are increasingly often combined with other medications to improve the effectiveness of therapy. We analyzed the characteristics of pravastatin, simvastatin, atorvastatin, pitavastatin, lovastatin, mevastatin, fluvastatin, and rosuvastatin obtained from the PubChem Substance database. On the basis of data related to chemical s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Simvastatin, and not pravastatin, has been shown to inhibit the proliferation of oesophageal adenocarcinoma and squamous cell carcinoma cells [62]. It differs from other statins in its relatively high hydrophilicity [63]. Interestingly, a large randomized trial showed an increase in cancer incidence among elderly people treated with pravastatin [64] (a detailed meta-analysis and meta-regression analysis of randomized controlled trials was performed).…”
Section: Discussionmentioning
confidence: 99%
“…Simvastatin, and not pravastatin, has been shown to inhibit the proliferation of oesophageal adenocarcinoma and squamous cell carcinoma cells [62]. It differs from other statins in its relatively high hydrophilicity [63]. Interestingly, a large randomized trial showed an increase in cancer incidence among elderly people treated with pravastatin [64] (a detailed meta-analysis and meta-regression analysis of randomized controlled trials was performed).…”
Section: Discussionmentioning
confidence: 99%
“…Elevated levels of TC and TG are strongly allied with CVD [10,119]. The discovery of statins takes pace and as of, some statins are on the market: atorvastatin, fluvastatin, lovastatin, pitavastatin, pravastatin, rosuvastatin and simvastatin [120]. Many combinatorial preparations of statins and other agents, such as ezetimibe/simvastatin, are also in the market.…”
Section: Statins and Their Discoverymentioning
confidence: 99%
“…The measurements were conducted at three different temperatures: 20, 25 and 37 • C. We chose representatives of both types of these drugs, based on some clear structural differences. We used two statins of type 1, namely pravastatin (hydroxy acid form) and simvastatin (lactone form), while we chose three statins of type 2, namely atorvastatin and rosuvastatin, because they are the most different from other statins in terms of chemical structure and physicochemical properties, and fluvastatin, which is highly similar to pitavastatin [60].…”
Section: Investigation Of Statin-hak1 Interactions Using Fluorescence Spectroscopymentioning
confidence: 99%